When Leadership and Spiritual Direction Meet: Stories and Reflections for Congregational Life - Stafford, Gil W.; Sample, Tex (Rowman & Littlefield Publishers, 2014)
Modern church leaders need to cultivate innovative and creative leadership skills, as they navigate today’s post-Christian world, and as their congregations look to them for insight and guidance. Gil Stafford takes a fresh look at this vital need, drawing upon his experience as a college coach, university president, and parish priest, and interweaving them with ancient spiritual practices found within the discipline of spiritual direction. Personal anecdotes help the reader envision their own life-transforming pilgrimage, as they develop into the type of adaptive leader that churches need in today’s rapidly changing world. This book challenges church leaders to foster sacred safe space, holy listening, silence, and wisdom storytelling, in order to create a discerning church community. These techniques of spiritual direction can be applied to every aspect of the church, from small group studies to conducting parish business. Gradually the leader will be able to delegate some of his responsibilities to the congregation, liberating them to be leaders, and rescuing him from trying to be all things to all people.